Some inequalities for cr-log-h-convex functions - Liu, Wei; Shi, Fangfang; Ye, Guoju; Zhao, Dafang (Journal of inequalities and applications, 2022)
The main purpose of this paper is to study certain inequalities for cr -log- h -convex functions with an interval value. To this end, we first give a definition of cr -log- h -convexity of interval-valued functions under the cr -order and study some properties of such functions. On this basis, we establish the Jensen-, Hermite–Hadamard-, and Fejér-type inequalities for cr -log- h -convex functions, and discuss some special cases. In addition, we give some numerical examples to illustrate the accuracy of the results obtained.